La catégorisation, entre cognition et interaction - Marianne Zogmal; Laurent Filliettaz (Nantes Université, 2018)
The purpose of this conclusion is to return to some of the theoretical presuppositions conveyed by the texts presented in the context of this volume, and to initiate a dialogue with an alternative perspective, that of interaction analysis. Despite elements of variation and even controversies, the articles converge, in some respects, on how to conceptualize the topic of categorization as a phenomenon of cognitive nature. They also take a clear stand, on the ways in which these cognitive phenomena articulate themselves with the concepts of action, temporality and language, in particular. After having identified these transversal elements that enable to "categorize" the texts produced, we propose to consider the topic of categorization as contingent on the conditions of its implementation in the verbal and nonverbal interactions. A distinct analytic lens is then proposed, which leads to overturning, or at least putting in perspective the presuppositions of a cognitive approach to categorization. To illustrate our point, we conclude this article by presenting some empirical data pertaining to the field of early childhood education. We show that categorization processes are at work permanently, and act dynamically as conditions for coordination in action.